Maslahah and Socioeconomic Growth: Distribution of Philanthropic Funds at Al-Falah Grand Mosque Sragen, Indonesia - May Shinta Retnowati; M. Adib Hamzawi (PC Ikatan Sarjana Nahdlatul Ulama Ponorogo, 2025)
Beyond its function as a place of worship, the mosque can also serve as a centre for managing philanthropic funds to support economic welfare. This study aims to examine how economical support activities from mosque-managed funds, such as zakat, infaq, and shodaqoh, contribute to socioeconomic development and poverty alleviation. Using a qualitative descriptive method, the findings reveal that fund distribution, either institutional or individual, has adapted to technological advancements, including such a program at Al-Falah Grand Mosque, Sragen, Indonesia, to distribute rice weekly to local beneficiaries using a card-based ATM system. Despite limited resources, it contributes positively to social welfare and quality of life improvement. Selain berfungsi sebagai tempat ibadah, masjid juga berperan sebagai pusat pengelolaan dana filantropi guna mendukung kesejahteraan ekonomi. Penelitian ini bertujuan untuk mengkaji bagaimana kegiatan ekonomi yang didanai oleh masjid, seperti zakat, infaq, dan shodaqoh, dapat mendorong pertumbuhan sosial ekonomi dan pengentasan kemiskinan. Menggunakan metode kualitatif deskriptif, hasil penelitian menunjukkan bahwa penyaluran dana dilakukan secara langsung maupun melalui lembaga, serta telah beradaptasi dengan perkembangan teknologi. Salah satunya adalah program ATM Beras di Masjid Al-Falah Sragen yang menyalurkan beras secara berkala kepada mustahik dengan sistem kartu. Meskipun dana terbatas, program ini memberikan kontribusi positif terhadap peningkatan kesejahteraan dan kualitas hidup masyarakat sekitar.